A Flexible and Moisturizing Multilayer Microporous Sponge Copolymerized with Keratin and Alginate. Issue 40 (25th October 2021) - Dai, Fengli; Li, Tao; Zhang, Yaping; He, Yufeng; Song, Pengfei; Wang, Rongmin
Abstract: Feather keratin (FK), a kind of low‐cost natural biopolymer with strong mechanical properties, was pretreated by sodium hydroxide solution, and then reacted with N‐hydroxy succinimide (NHS) coupled sodium alginate (SA) (SA‐NHS), which afforded multilayer microporous materials (FK‐SA sponge) of keratin combining alginate, and its performance as wound dressing was measured. Its structure and properties were characterized by Fourier‐Transform infrared spectroscopy (FT‐IR), thermogravimetric analysis/differential scanning calorimetry (TG/ DSC), scanning electron microscopy (SEM), absorption capacity, water retention and water vapor transmittance. The antimicrobial properties and release behavior were also studied. Under the condition of pH 7.4, the cumulative release rate of model drug‐loaded FK‐SA sponge got to 74 % within 13 hrs. Meanwhile, FK‐SA sponge supported benzalkonium chloride, a typical broad‐spectrum bactericide, has excellent antibacterial activity and unique biodegradability. That means this multilayer microporous sponge is expected to be used as wound dressing in the clinical nursing field and continuous drug delivery carrier in the biomedical field. Abstract : The feather keratin (FK) was pretreated, and reacted with N‐hydroxy succinimide (NHS) coupled sodium alginate (SA) (SA‐NHS), which afforded the multilayer microporous sponge (FK‐SA sponge) of FK combining SA. It was found the incorporation of SA had improved the swelling property, water retention rate, and permeability. At the same time, FK‐SA sponge had good antibacterial and release properties when loaded with benzalkonium chloride.